KEMAMPUAN KARYAWAN DALAM PENGGUNAAN SISTEM INFORMASI MANAJEMEN BERBASIS WEBSITE PADA SMKN 2 BANDA ACEH - Lailatussaadah Lailatussaadah (Jurnal Ilmiah Didaktika, 2013)
Website-based management information system (SIM) is a data processing system in an organization which has functions to collect, process, store, and provide accurate data on time. An employee’s skill in using website-based SIM is necessary as a the key factor. The aim of this research is to know the ability of employees to use website-based SIM, 2) the implementation of website-based SIM, and 3) the the challenges in using website-based SIM. This research is using a descriptive method and qualitative approach. The data were gathered by using observation, interview, and document analysis. The subjects of the research are employee, headmaster, the chief of administration, teacher, and student. The result shows that 1) the employee are skillful in collecting, entrying, storing, processing, and providing data in the website and are able to finish their job effectively. 2) website-based SIM has a role in school development among others as it can collect, store, and provide infomation, analyze students’ prestige by using prestige standard calculation, simplifies the prospective students to know the information about the department that suit with their preferences and talent, also provides an up- to-date data for their alumni. 3) the difficulties faced by the employees in using website-based SIM are: some employees who are still incapable of operating computer and internet, small amount of bandwidth provided by JARDIKNAS, unstable electricity and website that often went down, and spyware and malware threats.